2016
DOI: 10.1007/s12026-016-8787-9
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide inhibits PKCθ by regulating its phosphorylation and translocation to lipid rafts in Jurkat cells

Abstract: Protein kinase C theta (PKCθ) is a novel, calcium-independent member of the PKC family of kinases that was identified as a central player in T cell signaling and proliferation. Upon T cell activation by antigen-presenting cells, PKCθ gets phosphorylated and activated prior to its translocation to the immunological synapse where it couples with downstream effectors. PKCθ may be regulated by ceramide, a crucial sphingolipid that is known to promote differentiation, growth arrest, and apoptosis. To further invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…Similarly, mitochondria-associated neutral sphingomyelinase, the mammalian orthologue of Isc1, was shown to be activated by anionic phospholipids, especially phosphatidylserine and mitochondrial CL (42). In mammals, ceramide activates PKC-(43, 44) but inhibits PKC-and PKC-␦ in mammals (45,46). Yeast has only one PKC (Pkc1) isozyme, and its regulation by ceramide has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mitochondria-associated neutral sphingomyelinase, the mammalian orthologue of Isc1, was shown to be activated by anionic phospholipids, especially phosphatidylserine and mitochondrial CL (42). In mammals, ceramide activates PKC-(43, 44) but inhibits PKC-and PKC-␦ in mammals (45,46). Yeast has only one PKC (Pkc1) isozyme, and its regulation by ceramide has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…These platforms form a unique microenvironment with biophysical properties that allow them to trap and cluster receptor molecules and intracellular signaling molecules, thereby permitting and amplifying signal transduction (3,13,(15)(16)(17). Ceramide also directly interacts with cathepsin D, phospholipase A 2 , kinase suppressor of Ras, and protein kinase C isoforms (21,24,27,68). Recent studies have indicated that the Asm-ceramide system has an important role in regulation of macrophage functions, such as phagosome maturation (64a), cytokine release (28), and apoptosis (53,69).…”
Section: Introductionmentioning
confidence: 99%
“…Human Ether-a-go-go Related Gene (HERG) potassium channels play an important role in repolarization in cardiac action potentials. However, recent evidence has suggested a role for HERG in the proliferation and progression of multiple types of cancers, which may make it an attractive target for cancer therapy [1] . It has been confirmed that the existence of encoded potassium ion channels within tumor cell membranes has the ability to control the communication current of the cells.…”
mentioning
confidence: 99%